INFLUENCE OF COMPONENTS (UV + VIS) OF SOLAR RADIATION ON THE COLOR CHANGE OF UNSTEAMED AND STEAMED BEECH WOOD (Innovation in Woodworking Industry and Engineering design, 2026)
The paper presents the differences of color changes of unsteamed and steamed beech wood with saturated water steam with temperature t = 135 °C for τ = 7.5 h caused by long-term ex-posure of sunlight to the surface of wood in interiors for 36 months. Light white-gray color with a yellow tinge of native beech wood with values on the coordinates of the color space CIE L*a*b* (L* = 76.6, a* = 7.8, b* = 19.8) darkened due to sunlight and the wood turned pale-brown color with a touch of yellow (L* = 71.3, a* = 12.2, b* = 26.8). The degree of darkening and browning is quantified by the value of the total color difference ΔE* = 13.0. The deep brown-red color of steamed beech (L* = 55.3, a* = 14.5, b* = 23.5) brightened during exposure due to sunlight and the wood surface took on a pale brown hue (L* = 77.6, a* = 14.1, b* = 27.8). The degree of lightening of the color of steamed beech wood in the color space CIE L*a*b* is quantified by the value of the total color difference ΔE* = 7.1. A comparison of the color changes of native and steamed beech wood through the total color difference ΔE* due to daylight shows that the surface of steamed beech wood shows 52.2% smaller changes than unsteamed beech wood. The lower value of the total color difference of steamed beech wood indicates the fact that changes in beech wood chromophores caused by steaming steam have a positive effect on color aging due to natural aging and partial resistance of steamed beech to the initiation of photochemical reactions caused wavelengths UV+VIS sunlight.